O PERFIL PROFISSIONAL DO SUPERVISOR DE ENSINO - Sáez, Andrea Bueno (2008)
In a sociological perspective, this work aims to identify the profile of the supervisor of education that serves the Secretary of State for Education of São Paulo, checking that their actions are dedicated to teaching or administrative, and what the political and educational concepts these professionals. Supporting up to Tragtenberg, Silva Jr and Huert among other authors who deal specifically, the supervision of teaching, it is making a historical review of the legislation, spreadsheets and data that were collected through depositions and interviews with supervisors, Effective teaching of three Diretorias of Education of Greater Sao Paulo. The result of the research points to the predominance of a profile and bureaucratic oversight in the action of the supervisor of education, as well as implementing public policies and not partícipe their development. The supervisor of education is a representative of a political power that favors a certain order, even if there is an attempt to overrun a unilateral representation in the supervision of education.(AU)